Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1371/journal.pgen.1009378
|View full text |Cite
|
Sign up to set email alerts
|

RanBP2/Nup358 enhances miRNA activity by sumoylating Argonautes

Abstract: Mutations in RanBP2 (also known as Nup358), one of the main components of the cytoplasmic filaments of the nuclear pore complex, contribute to the overproduction of acute necrotizing encephalopathy (ANE1)-associated cytokines. Here we report that RanBP2 represses the translation of the interleukin 6 (IL6) mRNA, which encodes a cytokine that is aberrantly up-regulated in ANE1. Our data indicates that soon after its production, the IL6 messenger ribonucleoprotein (mRNP) recruits Argonautes bound to let-7 microRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 82 publications
2
36
0
Order By: Relevance
“…How mutations in RanBP2/Nup358 contribute to disease remains unclear. Our recently published work suggests that RanBP2/Nup358 represses the translation of two ANE1-associated cytokine mRNAs, IL-6 and TNF-α , by sumoylating argonaute proteins thereby enforcing microRNA-mediated silencing ( 240 ). Our data indicate that argonautes initially interact with the IL-6 mRNA in the nucleus, and that after nuclear export, RanBP2-dependent sumoylation stabilizes argonaute binding to the mRNA as part of an mRNP remodeling event.…”
Section: Orthomyxovirusesmentioning
confidence: 99%
“…How mutations in RanBP2/Nup358 contribute to disease remains unclear. Our recently published work suggests that RanBP2/Nup358 represses the translation of two ANE1-associated cytokine mRNAs, IL-6 and TNF-α , by sumoylating argonaute proteins thereby enforcing microRNA-mediated silencing ( 240 ). Our data indicate that argonautes initially interact with the IL-6 mRNA in the nucleus, and that after nuclear export, RanBP2-dependent sumoylation stabilizes argonaute binding to the mRNA as part of an mRNP remodeling event.…”
Section: Orthomyxovirusesmentioning
confidence: 99%
“…Previous studies have shown a role for Nup358 in the miRNA pathway (Sahoo et al, 2017;Shen et al, 2021). Disruption of the miRNA pathway via depletion of GW182 (Pfaff and Meister, 2013) did not affect ERMCS dynamics (Supplementary Fig.…”
Section: Nup358 Depletion Increases the Contacts Between Er And Mitochondriamentioning
confidence: 74%
“…The pathophysiology includes cytokine storm, exemplified by increased levels of pro-inflammatory cytokines such as INF-α and IL-6 in the serum and cerebrospinal fluid of the patients (Levine et al, 2020). Impairment in the miRNA-mediated translation regulation by Nup358 might contribute to the development of ANE-1 (Deshmukh et al, 2021;Shen et al, 2021). However, the functions for AL-associated Nup358 revealed by our studies may provide an additional platform for a better understanding of the pathogenesis of ANE-1.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we documented that RanBP2 promotes the microRNA-mediated suppression of ANE1-associated cytokines, such as IL6 and TNF-α [ 30 ]. We found that RanBP2 sumoylates Argonaute proteins thereby promoting their ability to silence the IL6 mRNA.…”
Section: Pathogenesis Of Ane1: Roles Of Ranbp2 In Ane1mentioning
confidence: 99%
“…The formation of the tight RanBP2/SUMO-RanGAP1/Ubc9 complex at the cytoplasmic filaments of the NPC is essential for the SUMO E3-ligase activity of RanBP2 [ 14 ]. Aside from mediating sumoylation, RanBP2 has been implicated in many aspects of cellular processes, including nucleocytoplasmic transport [ 15 , 16 , 17 , 18 ], trafficking of photoreceptors [ 19 , 20 ], glucose metabolism [ 21 ], attachment of microtubules to kinetochores during mitosis [ 22 , 23 , 24 , 25 ], myogenesis [ 26 , 27 ], and mRNA metabolism [ 18 , 28 , 29 ], as well as microRNA-induced silencing [ 30 , 31 , 32 , 33 ]. Beyond the nuclear pore, RanBP2 also appears to form cytosolic aggregates, which may include annulate lamellae and/or some other biomolecular condensates [ 31 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%